Question

Verify that the function y=x^2+c/x^2 is a solution of the differential equation xy′+2y=4x^2, (x>0). b) Find...

Verify that the function

y=x^2+c/x^2

is a solution of the differential equation

xy′+2y=4x^2, (x>0).

b) Find the value of c for which the solution satisfies the initial condition y(4)=3.

c=

Homework Answers

Know the answer?
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coins

Coins can be redeemed for fabulous gifts.

Not the answer you're looking for?
Ask your own homework help question
Similar Questions
Consider the differential equation x2y''+xy'-y=0, x>0. a. Verify that y(x)=x is a solution. b. Find a...
Consider the differential equation x2y''+xy'-y=0, x>0. a. Verify that y(x)=x is a solution. b. Find a second linearly independent solution using the method of reduction of order. [Please use y2(x) = v(x)y1(x)]
Find the solution of the Differential Equation X^2y''-xy'+y=x
Find the solution of the Differential Equation X^2y''-xy'+y=x
Verify that the indicated function is a solution of the given differentialequation.x2y′′−xy′+ 2y= 0;y=xcos (lnx), x...
Verify that the indicated function is a solution of the given differentialequation.x2y′′−xy′+ 2y= 0;y=xcos (lnx), x >0
1. Find the general solution to the differential equation y''+ xy' + x^2 y = 0...
1. Find the general solution to the differential equation y''+ xy' + x^2 y = 0 using power series techniques
Verify that the given function is the solution of the initial value problem. 1. A) x^3y'''-3x^2y''+6xy'-6y=...
Verify that the given function is the solution of the initial value problem. 1. A) x^3y'''-3x^2y''+6xy'-6y= -(24/x) y(-1)=0 y'(-1)=0 y''(-1)=0 y=-6x-8x^2-3x^3+(1/x) C) xy'''-y''-xy'+y^2= x^2 y(1)=2 y'(1)=5 y''(1)=-1 y=-x^2-2+2e^(x-1-e^-(x-1))+4x
a) Find the general solution of the differential equation y''-2y'+y=0 b) Use the method of variation...
a) Find the general solution of the differential equation y''-2y'+y=0 b) Use the method of variation of parameters to find the general solution of the differential equation y''-2y'+y=2e^t/t^3
Solve the Homogeneous differential equation (7 y^2 + 1 xy)dx - 1 x^2 dy = 0...
Solve the Homogeneous differential equation (7 y^2 + 1 xy)dx - 1 x^2 dy = 0 (a) A one-parameter family of solution of the equation is y(x) = (b) The particular solution of the equation subject to the initial condition y(1) =1/7.
Find the differential Equation of xy'-2y+(2x^3)e^-x=0
Find the differential Equation of xy'-2y+(2x^3)e^-x=0
Verify that y=x2 ln(x), is a solution of the differential equation x2y''-2y=3x2
Verify that y=x2 ln(x), is a solution of the differential equation x2y''-2y=3x2
Let y be the solution of the equation a) y ′ = 2 x y, satisfying...
Let y be the solution of the equation a) y ′ = 2 x y, satisfying the condition y ( 0 ) = 1. Find the value of the function f ( x ) = ln ⁡ ( y ( x ) ) at the point x = 2. b) Let y be the solution of the equation y ′ = sqrt(1 − y^2) satisfying the condition  y ( 0 ) = 0. Find the value of the function  f ( x...